Test Of Bio-Activator Model with Natural Zeolite from South Sulawesi As Filter Media and Adsorbents Heavy Metal Pb, Ni, and Cu - Sukmasari Sukma Antaria; Mary Selintung; Muh Saleh Pallu; Mukhsan Putra Hatta (Institut Teknologi Sepuluh Nopember, 2014)
The purpose of this study is how the characterization of natural zeolite South Sulawesi and how the ability of zeolite as filter media and adsorbents to reduce the heavy metal lead ( Pb ), Nickel (Ni) and Copper (Cu) in the raw water . Zeolites in activation , given the warming that is: 100º C , 200º C , 300º C , and 400º C , then in the characterization by SEM and XRD. Subsequently smoothed with a 170 mesh size ( 3 mm ) , and weighed each one weighing 50 grams and incorporated into any model of Bio - Activators, respectively on the tube , 2 , 3 and 4. Raw water that has been injected with 5 ppm Pb, Ni, Cu heavy metal inserted into the reservoir, then piped or for running into the model to test the ability of zeolite as filter media and adsorbents . Results if the water was tested by means of AAS (Atomic Absorption Spectroscope), instrument test results obtained from the numbers the actual decrease in the concentration and absorbance . Results actual dcrease in the concentration and adsorbance for each heavy metals Pb, Ni and Cu are : -0.2119, -0.1112, and -0.2902. Model analysis is the method of Langmuir and Freudlich. This result is expected to provide new information about the characteristics of natural zeolite South Sulawesi and produced water treatment models are inexpensive and easy to obtain.